STRATEGI PENINGKATAN PRODUKTIVITAS TANAMAN KELAPA SAWIT MELALUI PENDEKATAN MANAJEMEN BLOK DI PERKEBUNAN KELAPA SAWIT SKALA LUAS - Megawati Siahaan; Hardy Wijaya (Institut Teknologi Sawit Indonesia, 2020)
Increasing the productivity of oil palm is one of criteria success for field assistant in manage of afdeling/division. Field assistant in oil palm plantation has responsibility to control 500-800 ha depend on the policy of company. All acreage are divided block by block which size is 25-30 ha each. Block is designed to be homogeneous by arrange plant, silt, road, and etc appropriate the criteria, that makes easy to manage. But the facts, blocks has various for one to another and then must be handling with various way. Management Block Approach is one of the best way to evaluate and find the root cause. This methode can use to increase oil palm productivity. Problems in blocks not singular but many factors must be analysis. 3 Steps use in management block are gap analysis, analysis of root cause by fishbone method and Problem Identifications and Corrective Action (PICA) concepts. This method have tried in many company.